Speckle tracking imaging combined with myocardial comprehensive index to evaluate left ventricular function changes in patients with systemic lupus erythematosus. Issue 9 (23rd September 2021) - Feng, Jia; Zhai, Zijing; Wang, Zhen; Huang, Lei; Dong, Shanshan; Liu, Kuichan; Shi, Wenrong; Lu, Guilin; Qin, Wenjuan
Abstract: Objective: To evaluate early changes in left ventricular systolic function in patients with systemic lupus erythematosus (SLE) using three‐dimensional speckle tracking imaging (3D‐STI). Methods: A total of 30 SLE patients and 30 healthy people (control group) were selected, the patients were further divided into subgroups according to their Safety of Estrogens in Lupus Erythematosus National Assessment version of the SLE Disease Activity Index (SELENA‐SLEDAI) score: ≤ 12: mild‐to‐moderate group; > 12: severe group. All participants were examined using 3D‐STI, the 3D‐STI parameters were obtained. Receiver operating curves ( ROC ) were prepared for above parameters and analyzed to identify correlations among 3D‐STI parameters and high sensitivity‐TropT (hs‐TropT). Results: Compared with the control group, the absolute values of left ventricular end‐diastolic volume (LVEDV), left ventricular ejection fraction (LVEF), global longitudinal strain (GLS), global circumferential strain (GCS), left ventricular twist angle (LVtw), torsion (Tor) and myocardial comprehensive index (MCI) decreased, left ventricular end diastolic mass (LV EDmass), left ventricular end systolic mass (LV ESmass) and peak strain dispersion (PSD) increased in the mild‐to‐moderate and the severe groups ( P2   < 0.05, P3   < 0.05). There was statistically significant difference in terms of 3D‐STI parameters between the mild‐to‐moderate group and the severe group ( P1  < 0.05). The highest area under the ROC for MCI was 0.909, the highest sensitivity for MCI was 90.00%, and the highest specificity for Tor was 86.67%. Correlation analysis showed that there was a good correlation between the MCI and hs‐TropT ( r  = − 0.677). Conclusion: 3D‐STI technology may help detect early changes in left ventricular systolic function in patients with SLE.